Abundance mindset boosts leadership potential. Issue 6 (21st August 2022) - Hope, Joan
Abstract : When Laura Freebairn‐Smith was conducting research for her doctorate, she worked with John Pepper, who served as Chief Executive Officer of Proctor & Gamble. While thinking through other questions about leadership, the one she kept coming back to was "Why is he so great to work for?" He was "energetically a joy to be with" and exuded a sense that everything would be fine.